The role of ion channels in T cell function and disease - Manolios, Nicholas; Papaemmanouil, John; Adams, David J. (Frontiers in Immunology, 2023)
T lymphocytes (T cells) are an important sub-group of cells in our immune system responsible for cell-mediated adaptive responses and maintaining immune homeostasis. Abnormalities in T cell function, lead the way to the persistence of infection, impaired immunosurveillance, lack of suppression of cancer growth, and autoimmune diseases. Ion channels play a critical role in the regulation of T cell signaling and cellular function and are often overlooked and understudied. Little is known about the ion "channelome" and the interaction of ion channels in immune cells. This review aims to summarize the published data on the impact of ion channels on T cell function and disease. The importance of ion channels in health and disease plus the fact they are easily accessible by virtue of being expressed on the surface of plasma membranes makes them excellent drug targets..